The Virtuous Manager: A Vision for Leadership in Business - Flynn, Gabriel (Journal of business ethics, 2008)
This article seeks to contribute to a vision for leadership in business based on a recovery of virtue. The vision for leadership articulated here draws principally on the writings of the classical philosopher Aristotle and of the contemporary philosopher Josef Pieper. Without discounting the ever-increasing complexity of modern business, this essay will attempt to reconstruct Aristotle’s emphasis on virtue and moral character, and argues for the philosopher’s relevance to modern management and corporate leadership. The paper concludes that the message of virtue is a message of hope and attempts to find plain language to articulate its value to those engaged in business or concerned with the formulation of government policy.